A detailed study of magnetic diffuse scattering in a low-dimension ferromagnet CePdSb - Dr Devashi Adroja; Dr Matthias Gutmann (ISIS Facility, 2019)
We have carried out detailed investigations on the ferromagnetic (FM) Kondo lattice CePdSb, in polycrystal as well as single crystal form (TC=17.5K) using magnetization, neutron diffraction, inelastic neutron scattering and heat capacity. This has turned out to be an extraordinary compound, which exhibits pronounced anomaly at 10 K, well below TC=17.5K in the heat capacity and small-angle neutron scattering (SANS) and very weak anomaly at TC. Surprisingly, the correlation lengths in the ab-plane as well as along the c-axis are finite between TC and 10 K and the correlation lengths diverse only below 10K. Our preliminary study of the diffuse scattering in CePdSb on PRISMA (RB 20357) reveals a clear presence of diffuse scattering at 12K. We propose here to carry out a detailed diffuse scattering study in CePdSb using the SXD diffractometer at various temperatures between 2K and 50K.
Keywords: STFC ISIS Neutron and Muon Data